К эколого-зоогеографической характеристике жуков семейства Coccinellidae лесной и лесостепной зон Левобережной Украины - Мизер, А.В. (Вестник зоологии, 1971)
In the territory of the left-bank Ukraine in the forest zone 31 species (25 general
of Coccinellidae are found, mainly forest and meadow niesophylls; in the forest-steppe
zone 52 species (26 genera) are found, chiefly mesophyllic forms. The European species
predominate.